A looming revolution: Implications of self-generation for the risk exposure of retailers - Marianna Russo; Valentin Bertsch (The Economic and Social Research Institute (ESRI), 2018)
Managing the risk associated with uncertain load has always been a challenge for retailers in electricity markets. Yet the load variability has been largely predictable in the past, especially when aggregating a large number of consumers. In contrast, the increasing penetration of unpredictable, small-scale electricity generation by consumers, i.e. self-generation, constitutes a new and yet greater volume risk. Using value-at-risk metrics and Monte Carlo simulations based on German historical loads and prices, the contribution of decentralized solar PV self-generation to retailers' load and revenue risks is assessed. This analysis has implications for the consumers' welfare and the overall efficiency of electricity markets.
Keywords: C10; C50; G10; Q42; Q48; 330; Electricity market; Solar photovoltaic; Self-generation; Retailers' risk; Monte Carlo CVaR